Work Discipline And Organizational Citizenship Behavior - Suhendar, Fikry Ramadhan; Komariyah, Imas; Sirajudin, Husni A. (Program Pascasarjana STIE Amkop Makassar, 2023)
In the BPAKD West Java Province, this study intends to investigate the impact of organizational commitment and self-efficacy toward organizational citizenship behavior. This study employs a sample of 49 respondents using a quantitative methodology. Purposive sampling was the sample method employed in this study. In the meantime, SPSS 25 software is used for the analysis technique, which employs multiple linear regression analysis along with instrument, model, and hypothesis testing. The findings of this research demonstrate that while self-efficacy has no discernible impact on corporate citizenship behavior, organizational commitment does. Keywoard: Organizational Commitment, Organizational Citizenhsip Behavior